TAXONOMY OF REACTIVE SPEECH ACTS - Плахотнюк, Наталя; Макаревич, Олег; Коваленко, Ірина; Лисянюк, Олена (SWorldJournal, 2024)
The anthropocentric orientation of modern linguistics leads to addressing the issue of the dependence of pragmatic and communicative characteristics of utterances on the position of a remark in dialogue. By applying conversational analysis, initiating and